Prospects of Developing Gigonomics in Conditions of Global Digitalization on Russian Labour Market - J. M. Polyakova (Вестник Российского экономического университета имени Г. В. Плеханова)
Digital transformation of all spheres of society, changing values, modes of production and consumption caused the emergence of new types of labour relations.  Gigonomics is a new social and economic model, which is characterized by spread of new types of non-standard employment based on part-time, remote work and short-term labour contracts. Today gigonomics develops very fast all over the world, as this model is appealing for employers in respect  of  cutting  costs  on  personnel  remuneration,  providing  safe  working  conditions  and  others.  Russia announced the entry into the age of digital economy on 28 July 2017, when the program ‘Digital Economy of the Russian Federation’ was adopted, therefore the goal of the research is to identify prospects of developing freelancing and crowdsourcing as principle types of economic relations of gigonamics on Russian labour market. To reach the set goal the author analyzes the current development of digitalization in industrialized countries and in Russia and studies the development of gigonomics, in particular freelancing and crowd-sourcing.